Redescription of the mysid Petalophthalmus armiger Willemoes-Suhm, 1875 (Crustacea: Mysida: Petalophthalmidae) and distribution off western Mexico - Hendrickx, M.e.; Hernández-Payán, J.c. (Zootaxa, 2018)
Specimens of Petalophthalmus armiger Willemoes-Suhm, 1875, were collected off western Mexico during a deep-water survey. Six males and 32 females were obtained from 18 sampling localities in western Mexico. The species is redescribed in detail, including illustrations of body and appendages, and SEM photographs of the mandibles. The new material indicates that P. armiger is widely distributed in the area and more common than previously thought in the eastern Pacific. Samples indicate that P. armiger inhabits water far offshore, where total depth exceeds 1000 m. Due to the lack of discrete samplings in the water column, however, the precise depth interval where P. armiger occurs cannot be defined.